Retroperitoneal neuroglial heterotopia: a case report and literature review - Zhong, Jianhua; Yang, Lijun; Lin, Jinhui; Wu, Ruifa; Liu, Wenguang; Xu, Qinfang; Ma, Da; Qu, Zhibo (Frontiers in Pediatrics, 2024)
Background Neuroglial heterotopia is a rare lesion composed of differentiated neuroectodermal cells that manifest in extracranial locations, with the majority of cases predominantly occurring in the head and neck region. Retroperitoneal neuroglial heterotopia is exceptionally rare, with isolated cases published in the scientific literature. Case report Here, we present the case of a 3-year-old girl who was admitted without clinical signs but presented with a palpable abdominal mass. Ultrasonography and computed tomography scans revealed a sizable cystic lesion within the retroperitoneal space. Subsequently, laparoscopic resection was performed. Histological examination unveiled neuroglial cell-lined cysts encompassing fibrous connective tissue, ganglia, glial tissue, and nerve bundles. Notably, distinct areas and cell types exhibited expression of S100, glial fibrillary acidic protein, and neuron-specific enolase. Follow-up assessments revealed no relapses or late complications. Conclusion In cases of retroperitoneal neuroglial heterotopia, most children may remain asymptomatic without any congenital anomalies. Despite their detectability through imaging, accurate preoperative diagnosis is seldom achieved. Generally, a favorable prognosis follows complete surgical resection, although further cases are required to confirm its long-term efficacy, necessitating extended follow-up for verification.